ANALYSING STRATEGIES FOR OVERCOMING CHALLENGES IN ESG PRACTICES: A COMPARATIVE CONCEPTUAL PAPER ON MALAYSIA AND INDONESIA - Mohamad Hanif Abu Hassan; Wahidah Shari; Muhammad Fadzly Zakaria; Nur Yuhainis Ab Wahab (International Journal of Accounting, Finance and Business, 2024)
This study critically examines sustainability awareness among Small and Medium Enterprises (SMEs) in Malaysia and Indonesia. With a primary focus on discerning influential factors and challenges, the research addresses the exclusion of SMEs from mandatory Environmental, Social, and Governance (ESG) compliance, prevalent in Malaysia's and Indonesia current regulatory landscape. As ESG becomes integral for financial assessments and global trade, the oversight raises fairness concerns. SMEs, vital contributors to both nations' GDPs, face potential challenges. Employing a mixed-methods approach, the study utilizes a detailed questionnaire and Focus Group Discussion (FGD) validation, aiming for a comprehensive model. Anticipated outcomes include identifying critical issues and presenting a holistic model to guide sustainable SME development. This model, valuable for policymakers, fills the gap in SME ESG implementation, ensuring equitable inclusion for economic resilience in Malaysia and Indonesia